Introduction of the Cluster Complex and Innovative-Interrelated and Interacting Management Models and Transportation Cotton and Textile Products (Eurasian Research Bulletin, 2022)
The article explores the methodological approaches to the implementation of the cluster complex and innovation-related through the use of econometric models of management and transportation of cotton and textile products. The authors of this article explore various integration structures for the formation of an industrial and production structure, give their assessment of the adequacy of the use of modern innovative technologies in relation to cotton and textile enterprises, as well as the storage and transportation of finished products (CTP and TGP). The paper proposes an innovative organizational and industrial structure of the cluster system and its logistics in the management of cotton and textile enterprises.